Hvem var de? En lokalhistorisk undersøgelse af de tidligste private gymnastik- og idrætstiltag i Århus og Randers - Lundbye, Steen Rosenvinge (Forum for Idræt, 2002)
Resultater fra Lundbyes speciale og lokalhistorisk forsknings relevans for den samlede idrætshistoriske opfattelse. Steen Rosenvinge Lundbye: Who were they? A Local historical study of the earliest private gymnastic and sports initiatives in Århus and Randers Why did people become members of a gymnastic or sport association at the end of the 19th century? If we study exclusively the professional groups to which members of Denmark’s earliest gymnastic and sports associations belonged, it becomes clear that business and office occupations represented a large majority. This has been interpreted as evidence for the fact that professional affiliations were a prerequisite for admission and membership of these associations. However, as the present article attempts to demonstrate, an overrepresentation of this kind does not necessarily mean that everything depended on professional relations. A detailed local historical study of the earliest members of Århus Gynmastic Association in 1880 and of Randers Gynmastic Association of 1872, focusing especially on members’ social and residential relations, shows that other factors can be indicated that might also have had considerable significance. In this way it appears that a large number of members had other features in common besides their profession. A very large proportion of them had addresses on the same land registry title, a situation which becomes particularly evident when all members addresses are drawn in on a land registry map. These results lead to the logical conclusion that an incoming member’s social circle had just as much influence on the chance of he or she becoming a member or not. In spite of the simplicity of this thesis, it has until now been bypassed by Danish researchers into sporting history, and it could be a benefit if other associations’ members could be studied in the similar way. Only by that means can we achieve clear answers to these questions.